U.S. foreign policy the paradox of world power - Hook, Steven W. (Sage/CQ Press, 2014)
The United States faces growing challenges to its primacy in the global balance of power. The very factors that have given rise to its dominance-a sense of exceptionalism, the sharing and fragmentation of political power, and the engagement of civil society in the foreign policy process-also create vulnerabilities for the country. Fast-moving developments overseas, meanwhile, won't wait for U.S. leaders to adopt perfect foreign policy strategies. The fourth edition of Steven W. Hook's U.S. Foreign Policy: The Paradox of World Power provides students with a concise and accessible overview of this foreign policy paradox, and highlights the challenges facing policy makers. Instructors and students will appreciate the book's new full-color interior, expanded graphics program with new and thoroughly updated tables, figures, maps and feature boxes, and end-of-chapter resources for further review and study.